Peningkatan Softskill Untuk Memasuki Dunia Kerja Bagi Siswa Akuntansi - ,; ,; , (JUDIKAT: Jurnal Pengabdian Kepada Masyarakat, 2024)
Vocational High School (SMK) graduates are prepared to work in the public or private sector, or to work independently as entrepreneurs. Students are provided with technical skills based on their chosen major, as well as soft skills. However, the need for soft skills often does not receive enough attention. The soft skills training program for accounting students at SMK N 9 West Jakarta aims to help students understand the importance of soft skills. Students are expected to practice using soft skills that will support them in finding or creating jobs, writing cover letters, and creating interesting, informative, and effective Curriculum Vitae (CV). They are also expected to be confident when facing job interviews. It is hoped that the results of this training and mentoring will demonstrate that students understand the importance of soft skills such as communication, self-confidence, respect, open-mindedness, and honesty in the work environment and in daily life.